The impact of financial reporting standards on performance of Certified Public Accountants: CPAs - ทองคง สิทธิศักดิ์; ศรีพิพัฒน์ มนัสพันธ์ (Journal of Industrial Business Administration, 2019)
The purpose of the research study to find the impact of financial reporting standards on performance of Certified Public Accountant: CPAs. The sample studied were 125 CPAs selected by random sampling systematic. The research instrument is questionnaire. The statistic used percentage, mean, standard deviation, t-test, and Anova. The research found that the most of them are female younger than 25-35 years old. The most of CPAs concentrated with financial reporting standards and performance. There were non-significant for comparison level of CPAs’s Performance with education, experience, and training. Moreover, the results found that significant for impact of financial reporting standards on performance of Certified Public Accounting: CPAs.